2021
DOI: 10.1002/anie.202006402
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Metal–Organic Frameworks in Electronic Sensors

Abstract: H ereceived his Ph.D. in organic chemistry from Fujian Institute of Research on the Structure of Matter under the direction of Prof. Tian-Lu Sheng. His research interests include MOF materials in functional electronic devices. Ye Zhou is an IAS Fellow and group leader in the Institute for Advanced Study,Shenzhen University.H is research interests include flexible and printed electronics, organic/inorganic semiconductors, surface and interface physics, nanostructured materials, and nanoscale devices for technol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 245 publications
0
42
0
3
Order By: Relevance
“…In the case of phthalocyanine-based MOFs, fewer examples are available in the literature, but significant progress has been made recently. In recent years, the number of works on their use as active layers of chemiresistive, magnetic, ferroelectric, colorimetric and luminescent sensors has been growing rapidly [ 86 , 87 , 88 ]. It has been shown that hybrid materials including porphyrinoid molecules have better sensitivity and lower detection limits than pristine MOFs.…”
Section: Sensing Layers For Detecting No In Aqueous Mediamentioning
confidence: 99%
“…In the case of phthalocyanine-based MOFs, fewer examples are available in the literature, but significant progress has been made recently. In recent years, the number of works on their use as active layers of chemiresistive, magnetic, ferroelectric, colorimetric and luminescent sensors has been growing rapidly [ 86 , 87 , 88 ]. It has been shown that hybrid materials including porphyrinoid molecules have better sensitivity and lower detection limits than pristine MOFs.…”
Section: Sensing Layers For Detecting No In Aqueous Mediamentioning
confidence: 99%
“…Fifth, the relatively high thermal and chemical stability of most MOFs guarantees a long lifetime of MOF‐based sensors. Although recent reviews have discussed either MOF‐based chemical sensors relying on luminescent enhancement/quenching, [ 20,39,40 ] or MOF‐based sensors only relying on the electrical‐transduction mechanism, [ 1b,41–43 ] or open framework materials (including MOFs and covalent organic frameworks) based electronic devices in a broad view, [ 7 ] a comprehensive review focusing on gas sensing of diverse MOF‐based devices based on the latest literature is absent.…”
Section: Introductionmentioning
confidence: 99%
“…Es wurde gezeigt, dass die elektrischen und optischen Eigenschaften von orientierungskontrollierten guest@MOF-Schicht oft stark von der Orientierung des eingeschlossenen Gastes abhängen. [7][8][9][10][11][12] Die Materialfunktion kann weiter durch den Grad der Porenfüllung, d. h. durch die Gastbeladung, eingestellt werden, die Berichten zufolge ein entscheidender Faktor für die elektrische Leitfähigkeit, [12,13] die Gasdurchlässigkeit von photoschaltbaren guest@MOF-Materialien, [14,15] oder Photolumineszenz ist. [16,17] Darüber hinaus wurde berichtet, dass strukturelle Veränderungen im MOF-Gerüst aufgrund der Anwesenheit von Gastmolekülen die Photolumineszenz beeinflussen.…”
Section: Introductionunclassified